STRATEGY FOR COUNTERING TERRORISM IN INDONESIA: STUDY ON THE FIRST TEN YEARS OF REFORM (2002-2012) - Robi Nurhadi (Universitas Nasional, 2023)
This study aims to look at how the strategy for handling terrorism is implemented in this phase by using three analysis variables: strengthening legal infrastructure, strengthening institutional capacity, and implementing policies for handling terrorism. The analysis of these three variables is related to the similarities between the labels used by terrorist groups and the majority religion in Indonesia, namely Islam; and the ongoing democratization in the second ten years of the phase of handling terrorism in Indonesia. By using a qualitative approach and literature studies as well as limited observations from researchers who lived in Indonesia during the research period, the following findings were produced: the Indonesian government's strategy of counterattack against the threat of JI's malignancy experienced a